Species-Specific Outcome in the Competition for Nitrogen Between Invasive and Native Tree Seedlings - Bueno, Andrea; Pritsch, Karin; Simon, Judy (Frontiers in Plant Science, 2019)
The outcome of competition for nitrogen (N) between native and invasive tree species is a major concern when considering increasing anthropogenic N deposition. Our study investigated whether three native (i.e. Fagus sylvatica, Quercus robur, and Pinus sylvestris) and two invasive woody species (i.e. Prunus serotina and Robinia pseudoacacia) showed different responses regarding morphological and physiological parameters (i.e. biomass and growth indices, inorganic vs. organic N acquisition strategies, and N allocation to N pools) depending on the identity of the competing species, and whether these responses were mediated by soil N availability. In a greenhouse experiment, tree seedlings were planted either single or in native-invasive competition at low and high soil N availability. We measured inorganic and organic N acquisition using 15N labeling, total biomass, growth indices, as well as total soluble amino acid-N and protein-N levels in the leaves and fine roots of the seedlings. Our results indicate that invasive species have a competitive advantage via high growth rates, whereas native species could avoid competition with invasives via their higher organic N acquisition suggesting a better access to organic soil N sources. Moreover, native species responded to competition with distinct species- and parameter-specific strategies that were partly mediated by soil N availability. Native tree seedlings in general showed a stronger response to invasive P. serotina than R. pseudoacacia, and their strategies to cope with competition reflect the different species’ life history strategies and physiological traits. Considering the responses of native and invasive species, our results suggest that specifically Q. robur seedlings have a competitive advantage over those of R. pseudoacacia but not P. serotina. Furthermore, native and invasive species show stronger responses to higher soil N availability under competition compared to when growing single. In conclusion, our study provides insights into the potential for niche differentiation between native and invasive species by using different N forms available in the soil, the combined effects of increased soil N availability and competition on tree seedling N nutrition, as well as the species-specific nature of competition between native and invasive tree seedlings which could be relevant for forest management strategies.